Pilar leiomyoma - Niloofar Mehrolhasani (Our Dermatology Online, 2015)
A 30 years old man presented to our dermatology clinic with complaint of multiple firm tender red brown masses on his leg. We did an excisional biopsy. Under high power examination there were interwoven bundles of spindle cells. The nuclei were elongated with blunt ends (cigar shape), so the patient was diagnosed with pilar leiomyoma. We recommended him to use gabapentin for pain relief.